Sequential use of vinorelbine followed by gefitinib enhances the antitumor effect in NSCLC cell lines poorly responsive to reversible EGFR tyrosine kinase inhibitors. Issue 12 (15th July 2015) - Dal Bello, M.G.; Alama, A.; Barletta, G.; Coco, S.; Truini, A.; Vanni, I.; Boccardo, S.; Genova, C.; Rijavec, E.; Biello, F.; Bottoni, G.; Sambuceti, G.; et al.
<x xml:space="preserve">Abstract</x> Preclinical studies have suggested that combining cytotoxic agents with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) to treat EGFR‐mutated tumors may increase their inhibitory effect depending on the order of drug administration. The antitumor efficacy of different treatment sequences using vinorelbine (VNB) and gefitinib (GEF) was investigated both in vitro and in vivo in non‐small cell lung cancer (NSCLC) cell lines with the rationale of potentially translating these findings into the clinical setting. The EGFR‐wild‐type A549 and the EGFR‐mutated (exon 21 L858R/exon 20 T790M) H1975 cell lines were treated as follows: GEF followed by VNB, VNB followed by GEF and the two drugs applied individually or concurrently. Results in vitro demonstrated that the sequence of VNB followed by GEF was significantly more active than single‐agent treatments. The expression of activated EGFR and its downstream pathway genes indicated that the increased cytotoxic effect of the VNB and GEF treatment sequence was accompanied by inhibition of EGFR, AKT and ERK1/2. Moreover, the increased inhibition of tumor growth after treatment with VNB followed by GEF was also confirmed in CD1‐nude mice that were xenotransplanted with H1975 cells (p < 0.0001). This effect was paralleled by a corresponding decrease in cancer glucose consumption, as assessed by micro‐positron emission tomography scans (p < 0.05). These preclinical findings in NSCLC cell lines, which are poorly responsive to EGFR‐TKIs, demonstrated that the sequential treatment of VNB followed by GEF induced a significant antitumor effect, which supports the translation of this treatment schedule into a clinical setting.